NUCLEAR CHANNEL SYSTEM (NCS) IN NORMAL ENDOMETRIUM AND AFTER HORMONAL STIMULATION - Novotny, Radko; Malinsky, Jiri; Oborna, Ivana; Dostal, Jiri (Biomedical papers, 1999)
The ultrastructure of NCS was investigated in two groups of patients (15 in each) during the secretory phase ofthe normal menstrual cycle and after the hormonal stimulation performed in the IVF programme by GnRH-a, FSHand hCG. Three developmental stages of the NCS were classified. The most numerous were the NCS in the maturestage (type 2), less in the early developmental stage (type 1) and least in the regression stage (type 3). Thesimultaneous occurrence of all three types does not conform the statement of Spornitz6. The proportions of thethree types were identical in both investigated groups of patients. The number of NCS (per 100 of nuclei) washigher in the group after hormonal stimulation than in the normal cycle. The quantitative measurement of the NCSshowed its larger size in the group after hormonal stimulation than in the normal cycle, but the differences in theshape were not significant. In the serial ultrathin sections we demonstrated the relation of NCS to the nucleolus andto the invaginations of the nuclear envelope, the formation of the electron lucent center and the spiral arrangementof the tubules. In the early regression stage we described the relation of the internal row of tubules to the formedmyelin figures. We suppose that the higher number and larger size of NCS can be taken as a sign of the increasedactivity of the endometrium during the early secretory phase after the hormonal stimulation.
Keywords: Endometrium / Human / Ultrastructure / NCS / Hormonal stimulation